2010
DOI: 10.1007/s10826-009-9348-9
|View full text |Cite
|
Sign up to set email alerts
|

Using a Mindfulness-Based Procedure in the Community: Translating Research to Practice

Abstract: Maladaptive behaviors, such as aggressive and disruptive behaviors, are a significant risk factor for maintaining community placement by individuals with intellectual disabilities. When experienced researchers provide training to individuals with intellectual disabilities on a mindfulness-based strategy, Meditation on the Soles of the Feet, the individuals are able to effectively self-manage their maladaptive behaviors. We investigated whether similar effectiveness would be found if community-based therapists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 29 publications
0
38
0
4
Order By: Relevance
“…The outstanding results of this study, reduction of aggressive behaviour to zero and a community living arrangement, showed the potential of mindfulness practice as an alternative to behavioural intervention for individuals with developmental disabilities (DD). Follow-up studies confirmed its use as a selfmanagement strategy for aggressive behaviours (e.g., Adkins, Singh, Winton, McKeegan, & Singh, 2010;Singh et al, 2011a;Singh et al, 2011b;Singh et al, 2007a), deviant sexual arousal (Singh et al, 2011c) and anxiety and obsessive thinking (Brown & Hooper, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…The outstanding results of this study, reduction of aggressive behaviour to zero and a community living arrangement, showed the potential of mindfulness practice as an alternative to behavioural intervention for individuals with developmental disabilities (DD). Follow-up studies confirmed its use as a selfmanagement strategy for aggressive behaviours (e.g., Adkins, Singh, Winton, McKeegan, & Singh, 2010;Singh et al, 2011a;Singh et al, 2011b;Singh et al, 2007a), deviant sexual arousal (Singh et al, 2011c) and anxiety and obsessive thinking (Brown & Hooper, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…More recently, Griffith et al (2016) suggested that interventions integrating mindfulness may be useful for people with ID, as unlike multicomponent procedures, the core of mindfulness is centred on one aspect: the ability to shift the focus of one's attention, allowing an individual time to calm themselves and choose how to react to a triggering thought or event (Adkins et al 2010). There are many definitions of mindfulness; however, it is generally understood as intentionally focusing one's attention on the present moment experience, in a non-judgemental and accepting way (Kabat-Zinn 1990).…”
mentioning
confidence: 99%
“…The research into mindfulness-based practices used with people with ID is more limited; however, researchers have reported reductions in physical and verbal aggression (Singh et al 2008); depression (Idusohan-Moizer et al 2015), anxiety and aggression (Adkins et al 2010); and deviant sexual arousal (Singh et al 2011). A systematic review (Hwang and Kearney 2013) and a systematic review and narrative analysis of mindfulness-based approaches for people with ID found a number of methodological limitations in the reviewed papers (some of which were included in both reviews).…”
mentioning
confidence: 99%
“…In the USA, Soles of the Feet (SoF) meditation has been developed as a way of making MBPs accessible to people with ID (Singh et al 2011) It has been successfully used in ID populations to self-manage anger and at long-term follow up has resulted in reported reductions or total elimination of aggressive behaviours (Adkins et al 2010;Singh et al 2003Singh et al , 2007Singh et al , 2008Singh et al , 2011. A systematic review found the most frequent objective of MBPs for people with ID was the reduction of aggressive behaviour (explored in 7/12 studies), and of these, all reported a reduction after participating in an MBP (Hwang and Kearney 2013).…”
mentioning
confidence: 99%